Genomic characterization of Phenylalanine ammonia lyase gene in buckwheat - Thiyagarajan, K.; Vitali, F.; Tolaini, V.; Galeffi, P.; Cantale, C.; Vikram, P. (Public Library of Science, 2016)
Phenylalanine Ammonia Lyase (PAL) gene which plays a key role in bio-synthesis of medicinally important compounds, Rutin/quercetin was sequence characterized for its efficient genomics application. These compounds possessing anti-diabetic and anti-cancer properties and are predominantly produced by Fagopyrum spp. In the present study, PAL gene was sequenced from three Fagopyrum spp. (F. tataricum, F. esculentum and F. dibotrys) and showed the presence of three SNPs and four insertion/deletions at intra and inter specific level. Among them, the potential SNP (position 949th bp G>C) with Parsimony Informative Site was selected and successfully utilised to individuate the zygosity/allelic variation of 16 F. tataricum varieties. Insertion mutations were identified in coding region, which resulted the change of a stretch of 39 amino acids on the putative protein. Our Study revealed that autogamous species (F. tataricum) has lower frequency of observed SNPs as compared to allogamous species (F. dibotrys and F. esculentum). The identified SNPs in F. tataricum didn’t result to amino acid change, while in other two species it caused both conservative and non-conservative variations. Consistent pattern of SNPs across the species revealed their phylogenetic importance. We found two groups of F. tataricum and one of them was closely related with F. dibotrys. Sequence characterization information of PAL gene reported in present investigation can be utilized in genetic improvement of buckwheat in reference to its medicinal value.